Identifying customers trust towards E-banking transaction: a study in CIMB bank Kuala Lumpur / Ahmad Zahrisy Sufian Mohamad - Mohamad, Ahmad Zahrisy Sufian (Faculty of Business and Management, 2012)
Internet banking is a vital and popular alternative in doing daily transaction. The growth of technology influences the people in using internet banking. Nowadays internet banking are becoming an increasingly important in daily life. Malaysia that have the fifth largest banking sector in Asian which is CIMB Group are the one of the banker who provide good internet banking namely CIMB Clicks. However only a few from million people in Malaysia are using internet banking. It is because the problem of trust that occur in using internet banking. The purpose of this research is to determine and understanding why trust problem occur in internet banking not only in Malaysia but also in the world. The researcher aim in assisting banking sector to improve the level of trust in using internet banking.